Post-partum Symphysis Pubis diastasis - Rai, Sangam; Pradhan, Peru; Dangal, Ganesh; Shrestha, Sona; Rajbhandari, Subrina; Yadav, Ranjana; Shah, Ranjana; Sherpa, Sona; Ansari, Rawab (Journal of Nepal Health Research Council, 2024)
Pubic symphysis is a non-synovial joint, made up of a fibrous cartilage disc connecting the two sides of pubic rami in the midline. During pregnancy under the influence of hormones particularly relaxin, the gap increases by 2 to3mm. When the diameter is more than 10 mm, it is considered as pubic symphysis diastasis. Pregnancy and childbirth are the most common causes of pubic symphysis diastasis followed by traumatic causes. Women with post-partum symphysis diastasis present during puerperium with inability to bear weight owing to severe supra-pubic and groin pain. They have complaint of severe excruciating pain while standing up or to perform any movement involving hip abduction. For the diagnosis, proper history regarding delivery should be sought followed by physical examination and radiological imaging. Most cases can be treated with conservative management which includes- use of analgesia and anti-inflammatory medicines for the pain management and stabilization of pelvis using brace/pelvic belt. Some may benefit from physiotherapy. In extreme cases, operative fixation may be required with the involvement of orthopedic surgeon.Keywords: post-partum symphysis diastasis; pubic symphysis; rare presentation.